A marine bio-functional lipid, fucoxanthinol, attenuates human colorectal cancer stem-like cell tumorigenicity and sphere formation - Terasaki, Masaru (J Clin Biochem Nutr, 2017)
Fucoxanthinol (FuOH), an intestinal metabolite form of fucoxanthin (Fx) isolated from marine algae, is known to possess multiple health benefits, such as prevention of human cancer. However, there is little available information about the effects of FuOH on colorectal cancer stem cells (CCSCs) and their contribution to drug resistance, tumorigenesis and cancer recurrence. In the present study, we investigated the anti-proliferative effect of FuOH on two putative CCSCs, CD44(high)/EpCAM(high) cells and colonospheres (Csps) formed by HT-29 human colorectal cancer cells, and the suppressive effects of FuOH on the growth of xenografted tumor. FuOH significantly inhibited the growth of CD44(high)/EpCAM(high) cells and disintegrated Csps and induced many condensed chromatin bodies in the cells in a dose-dependent manner. The IC(50) value of FuOH for these changes in Csps was 1.8 µM. FuOH down-regulated pAkt (Ser(473)), PPARβ/δ and PPARγ in Csps. These proteins play a critical role in cell proliferation, the cell cycle, metastasis and extracellular adhesion. Ten days after the administration of FuOH (5 mg/kg body weight) to the mice every 3 to 4 days significantly suppressed the Csps tumorigenesis when compared to the untreated control mice. Our results suggest that FuOH could be used as a chemopreventive agent against human CCSC.